Highly active nanostructured Co3O4 catalyst with tunable selectivity for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Vijayanand, Subramanian; Potdar, Hari S.; Joy, Pattayil Alias; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chemistry Letters, 2008)
This is a first report of highly efficient heterogeneous nanostructured Co3O4 catalyst (6-8 nm) having high surface area (95 m(2)/g) developed for selective liquid phase air oxidation of p-cresol under atmospheric pressure conditions.

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Rapid generation of hierarchical nanoarchitectures of CdS via facile microwave assisted hydrothermal/semi-solvothermal route - Shinde, Manish D.; Pawar, Amol U.; Sreeja, V.; Rane, Sunit; Potdar, Hari S.; Amalnerkar, Dinesh P. (International Journal of Nanotechnology, 2010)
1-D nanorod bundles as well as sea urchin and starfish like hierarchical morphological nanoarchitectures of CdS have been synthesised using a facile microwave assisted hydrothermal/semi-solvothermal technique. Observation of interesting regular/irregular pine-tree like secondary growth over these hierarchical nanoarchitectures is an important aspect of this work. Cadmium acetate and thiourea were used as precursor materials and were dissolved in solution containing mixture of diethylene triamine (DETA) and deionised water (DIW) in different volume ratios prior to subjecting the resultant solution to microwave radiation of 300 W at a reaction time of 10 min and temperature of 140 degrees C. XRD revealed formation of hexagonal CdS with strong (002) preferred orientation (c-axis orientation). Morphology dependent optical properties are studied using room temperature photoluminescence spectroscopy. We feel such secondary growth will be highly favourable in determining the non-linear properties of optoelectronic devices fabricated using such novel hierarchical nanoarchitectures.
Keywords: CdS; hierarchical nanoarchitectures; Microwave; Nanorods; secondary growth; solvothermal synthesis

Investigation of poly(o-anisidine)-SnO2 nanocomposites for fabrication of low temperature operative liquefied petroleum gas sensor - Patil, Dewyani; Kolhe, Kishor; Potdar, Hari S.; Patil, Pradip (Journal of Applied Physics, 2011)
Poly(o-anisidine)-tin oxide (POA-SnO2) nanocomposites has been investigated for the fabrication of low temperature operative (100 degrees C) liquefied petroleum gas (LPG) sensor. The POA-SnO2 nanocomposites have been synthesized through an in situ chemical polymerization of o-anisidine in presence of SnO2 nanoparticles. The POA-SnO2 nanocomposite shows better LPG sensing properties than that of pure POA. The nanocomposite with 50 wt. % SnO2 exhibits an excellent LPG sensing characteristics at the operating temperature of 100 degrees C such as higher relative gas response (similar to 23.47% to 3.4% of LPG), extremely rapid response (similar to 6 s), fast recovery (similar to 33 s), good reproducibility, and remarkable selectivity. The application of POA-SnO2 nanocomposites for fabrication of the LPG sensor was demonstrated. (C) 2011 American Institute of Physics. [doi:10.1063/1.3667107]

Nanostructured spinet ZnCo2O4 for the detection of LPG - Vijayanand, Subramanian; Joy, Pattayil Alias; Potdar, Hari S.; Patil, Dewyani; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
Nanostrucutred spinel ZnCo2O4 (similar to 26-30 nm) was synthesized by calcining the mixed precursor (consisting of cobalt hydroxyl carbonate and zinc hydroxyl carbonate) in air at 600 degrees C for 5 h. The mixed precursor was prepared through a low cost and simple co-precipitation/digestion method. The transformation of the mixed precursor into nanostructured spinel ZnCO2O4 upon calcinations was confirmed by X-ray diffraction (XRD) measurement, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HRTEM). To demonstrate the potential applicability of ZnCo2O4 spinel in the fabrication of gas sensors, its LPG sensing characteristics were systematically investigated. The ZnCo2O4 spinel exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 72-50 ppm LPG gas at 350 degrees C), response time (similar to 85-90 s), recovery time (similar to 75-80 s), excellent repeatability, good selectivity and relatively lower operating temperature (similar to 350 degrees C). The experimental results demonstrated that the nanostructured spinel ZnCo2O4 is a very promising material for the fabrication of LPG sensors with good sensing characteristics. Plausible LPG sensing mechanism is also discussed. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: HRTEM; LPG sensor; Nanostructured ZnCo2O4; Semiconductor gas sensors; XPS